Discourse Markers in Tertiary Level Students’ Essay Writing: Ability and Problems - Riznanda, Winny Agustia (Institut Agama Islam Negeri (IAIN) Curup, 2021)
Writing is a fundamental, yet complicated part of language learning. In writing, Discourse Markers is an indispensable component of writing quality. The aim of the present study was to find out how Discourse Markers (DM) were applied to build coherence in EFL studentsâ€™ essay writing and the problems encountered. Descriptive design was applied; analyzed 52 target DM and how they were used in 30 academic essay writing. The participants of the study were 30 students majoring in English Education of UIN Raden Fatah Palembang academic year 2019/2020. The results revealed that the participants employ 32 DM in 221 occurrences, in which 102 occurrences were inappropriately used. The problematic matters cover non-equivalent exchange (52 occurrences), and overuse (48 occurrences). Despite their awareness of the importance of DM to assure the coherence of their essays, they need to develop their ability to use DM correctly and efficiently to make their writing connected more logically.Â Keywords: discourse markers, coherence, essays.